NOTCH1-mutated chronic lymphocytic leukemia displays high endoplasmic reticulum stress response with druggable potential - Silva Barcelos, Estevão Carlos; Rompietti, Chiara; Adamo, Francesco Maria; Dorillo, Erica; De Falco, Filomena; Del Papa, Beatrice; Baldoni, Stefano; Nogarotto, Manuel; Esposito, Angela; Capoccia, Silvia; Geraci, Clelia; Sorcini, Daniele; et al. (Frontiers in Oncology, 2023)
Constitutive activation of NOTCH1-wildtype (NT1-WT) signaling is associated with poor outcomes in Chronic Lymphocytic Leukemia (CLL), and NOTCH1 mutation (c.7541_7542delCT), which potentiates the NOTCH1 signaling, worsens the prognosis. However, the specific mechanisms of NOTCH1 deregulation are still poorly understood. Accumulative evidence mentioned Endoplasmic Reticulum (ER) stress/Unfolded Protein Response (UPR) as a key targetable pathway in CLL. In this study, we investigated the impact of NOTCH1 deregulation on CLL cell response to ER stress induction, with the aim of identifying new therapeutic opportunities for CLL. We performed a bioinformatics analysis in NOTCH1-mutated (NT1-M) and NT1-WT CLL to identify Differentially Expressed Genes (DEGs) using the Rank Product test. Quantitative real-time polymerase chain reaction (qPCR), western blotting, cytosolic Ca2+, and Annexin-V/PI assay were used to detect curcumin ER stress induction effects. A median-effect equation was used for drug combination tests. Experimental mouse model Eμ-TCL1 was used to evaluate the impact of ER stress exacerbation by curcumin treatment on the progression of leukemic cells and NOTCH1 signaling. Bioinformatics analysis revealed a gene enrichment of components of ER stress/UPR pathway in NT1-M compared to NT1-WT CLL. Ectopic expression of NOTCH1 mutation upregulated the levels of ER stress response markers in PGA1 CLL cell line. Primary NT1-M CLL was more sensitive to the curcumin as documented by a significant perturbation in Ca2+ homeostasis and higher expression of ER stress/UPR markers compared to NT1-WT cells. It was also accompanied by a significantly higher apoptotic response mediated by CHOP expression, caspase-4 cleavage, and downregulation of NOTCH1 signaling in NT1-M CLL cells. Curcumin potentiated the apoptotic effect of venetoclax in NT1-M CLL cells. In Eμ-TCL1 leukemic mice, the administration of curcumin activates ER stress in splenic B cells ex vivo and significantly reduced the percentage of CD19+/CD5+ cells infiltrating the spleen, liver, and BM. These cellular effects were associated with reduced NOTCH1 activity in leukemic cells and resulted in prolonged survival of curcumin-treated mice. Overall, our results indicate that ER stress induction in NT1-M CLL might represent a new therapeutic opportunity for these high-risk CLL patients and improve the therapeutic effect of drugs currently used in CLL.